Análisis del precedente vinculante en materia tributaria en el Perú - Dávila Alvarado, César (2021)
The present work aims to carry out an analysis of various practical problems that legal operators face when working with precedents, especially in tax matters. The questions to be analyzed are: (i) Which of the interpretations made by the Constitutional Court and the Supreme Court are binding? (ii) In what sense are they binding? (iii) To what extent are they binding? and, (iv) who do they link?